Transitions from tradition: a case study of agricultural participation and its drivers in four communities in the Western Cape, South Africa - Bergen, Joshua (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScConsEcol)--Stellenbosch University, 2025.